2018
DOI: 10.1016/j.bbadis.2018.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Platelet microparticle delivered microRNA-Let-7a promotes the angiogenic switch

Abstract: Platelet microparticle (PMP)-induced angiogenesis plays a key role in tumour metastasis and has been proposed to contribute towards cardiovascular disease by enhancing atherosclerotic plaque vulnerability. However, the mechanisms underlying PMP induced angiogenesis are ill defined. Recent reports demonstrate that PMPs deliver micro-RNAs (miRNAs) to recipient cells, controlling gene expression. We therefore evaluated whether miRNA transfer was a key regulator of PMP-induced angiogenesis. Co-culturing PMPs with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 51 publications
1
56
0
2
Order By: Relevance
“…Platelet‐derived microvesicles were incubated with human umbilical vein endothelial cells (HUVECs), internalized by HUVECs, and the carrying microRNA let‐7a was transferred to HUVECs. The active substance microRNA let‐7a can directly target the 3′ untranslated regions (3′UTRs) of THBS‐1 and inhibit the release of THBS‐1, affecting the angiogenesis response . In addition, PMV infiltration in solid tumours, the anchoring to tumour cells and the metastasis of microRNAs result in the gene suppression of tumour cells, which can inhibit the growth of primary tumours and affect the immune response, the angiogenesis of tumours and other cancer‐related processes.…”
Section: Biological Effects Of Active Moleculesmentioning
confidence: 99%
“…Platelet‐derived microvesicles were incubated with human umbilical vein endothelial cells (HUVECs), internalized by HUVECs, and the carrying microRNA let‐7a was transferred to HUVECs. The active substance microRNA let‐7a can directly target the 3′ untranslated regions (3′UTRs) of THBS‐1 and inhibit the release of THBS‐1, affecting the angiogenesis response . In addition, PMV infiltration in solid tumours, the anchoring to tumour cells and the metastasis of microRNAs result in the gene suppression of tumour cells, which can inhibit the growth of primary tumours and affect the immune response, the angiogenesis of tumours and other cancer‐related processes.…”
Section: Biological Effects Of Active Moleculesmentioning
confidence: 99%
“…MVs also deliver angiogenic signals [27]: Transfer of miRNA let-7a or miR-27b in endothelial cells down-regulates the expression of the anti-angiogenic modulator thrombospondin-1, thus enhancing platelet-dependent endothelial tube formation [168,169].…”
Section: Platelet Microvesicle-derived Mirnasmentioning
confidence: 99%
“…It has long been reported that miRNAs are a significant cargo contained by MVs . Advances in this field will contribute to a better understanding of the role of delivered miRNAs in pathology and enable them to be identified as therapeutic targets …”
Section: Overview Of Mvs and Mirnasmentioning
confidence: 99%
“…These two kinds of miRNAs can inhibit migration and tube formation of HUVECs by targeting selectin‐P (SELP) and platelet‐derived growth factor receptor alpha (PDGFRα) to enhance vascular endothelial cell damage . Recently, a data showed for the first time that miR‐let‐7a delivered by PMV targeted the 3′ UTR of anti‐angiogenic thrombospondin‐1 (THBS‐1) mRNA and potently inhibited THBS‐1 protein synthesis to drive endothelial tubule formation in vitro …”
Section: The Role Of Mvs Containing Specific Mirnas In Vascular Endotmentioning
confidence: 99%
See 1 more Smart Citation